Potential Impact of Innovation on the Competitiveness of Sports - Madarász, Tamás (International Journal of Engineering and Management Sciences, 2020)
Innovation and development activities related to sports and the tools created during the processes facilitate performance sports players (athlete, coach, sports manager) to achieve outstanding results in their field.The success of sport can have a major impact on the social image of sport and its economic potential, and thus on the future of the sport. In my paper, I undertake to introduce the innovation processes associated with competitive sport and the products that result from these innovative activities, and then examine how and to what extent these supplies influence the economic and professional performance of the sports under investigation.